Evolução de conceitos de mundo: uma proposta para inserção da teoria da relatividade no ensino médio - Freire, Joseil Carvalho (2015)
This work presents the development and application of a proposal for inclusion of topics Theory of Special Relativity and General Relativity in high school. It also presents the results obtained during its application and a short discussion on them. The developed didatic sequence makes use of varied teaching tools, with emphasis on group work. The application of the didactic sequence occurred during regular class period, the morning shift, in three high school classes of first, second and third year. It was adopted as didatic material educational an alternative book for Physics Teaching, which uses a language closer to that used by the students. The Manga Guide to Relativity, which addresses, among other things, the concepts of the Theory of Special and General Relativity simply and understandable for students, making it the most attractive content. All work is grounded in constructivism, specifically the Meaningful Learning Theory of David Ausubel and Joseph D. Novak. The developed product is presented at the end of this work, and consists of a material for the teacher containing all activities, texts, suggested readings and links, as well as notes on the result of this first application.